Peran Home Industry Jamur Tiram Dalam Meningkatkan Pendapatan Para Pengusaha Jamur Tiram Pada Masa Pandemi Covid-19 - Farhana Muhammad; Isfi Sholihah; Agus Riswanto; Widiawati Prima Wardani (Universitas Hamzanwadi, 2021)
This research aims to; 1) Knowing the production process of the oyster mushroom home industry in increasing the income of entrepreneurs during the covid-19 pandemic, 2) Knowing marketing strategies in increasing the income of entrepreneurs during the covid-19 pandemic, 3) Knowing the home industry's obstacles in increasing the income of the entrepreneurs. entrepreneurs during the covid 19 pandemic, 4) Knowing the role of the oyster mushroom home industry in increasing the income of oyster mushroom entrepreneurs in the village of Beririjarak, Wanasaba sub-district in 2021. This research is a type of qualitative research using a descriptive approach. Data collection techniques used are observation, interviews, and documentation. Interviews were conducted directly to all respondents with a total of 9 oyster mushroom entrepreneurs. Based on the results of this study, the role of entrepreneurs in the production process starts from the mixing of raw materials and even marketing. And also the oyster mushroom industry plays an important role in improving the economy of oyster mushroom entrepreneurs meeting their daily needs. Because the increase in income between before and after this business reached 57%. However, the income of these oyster mushroom home industry entrepreneurs has had an impact due to the COVID-19 pandemic so that their income has decreased to 27%